Dynamic model of economic cycles origin - Matrosov, Valerij Vladimirovich; Shalfeev, Vladimir Dmitrievich (Известия высших учебных заведений: Прикладная нелинейная динамика, 2025)
The purpose of the work is to research the phenomenon of the self-oscillation of the economic cycles for the model of the network with different types of element couplings (cooperative and competitive). As the element of the production network there are considered the typical system of automatic control of the added value,which determines the profitability of production. Methods. The research methods of the theory of nonlinear dynamic systems. Results. Modeling of nonlinear dynamics of small ensembles of connected production elements indicates the significant role of connections, in particular, the antagonistic (competitive) relationships lead to the emergence of regular and irregular economic fluctuations (cycles).